Estrogen deficiency and periodontal condition in rats: a radiographic and macroscopic study - Anbinder, Ana Lia (2006)
The purpose of this study was to evaluate the impact of ovariectomy-induced estrogen deficiency as a risk factor of periodontal disease in rats. Forty 90-day old female rats were either ovariectomized (OVX; n=20) or sham operated (SHAM; n=20). After 30 days, periodontitis was induced by placement of a cotton ligature around the upper second molars of 10 OVX and 10 SHAM animals. All animals were sacrificed 5 weeks later. Body weight was assessed before all surgical procedures. The left hemimaxillas were removed and the percentage of periodontal bone support was determined radiographically and buccal alveolar bone loss was determined macroscopically using an image-analysis software. Furcation involvement was also evaluated. Data were analyzed statistically by ANOVA at 5% significance level. Within the evaluated period, the ovariectomized rats gained more weight than the sham-operated animals (p<0.001). The animals in which periodontitis was induced had less bone support, greater alveolar bone loss and furcation involvement than those without ligature (p<0.001). However, there was no difference between ovariectomized and sham-operated animals (p>0.05). Based on the findings of this study, estrogen deficiency could not be considered as a risk factor for periodontal disease.